2016
DOI: 10.1200/jop.2015.006999
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Patient-Provider Communication Among Cancer Survivors: Findings From a Nationally Representative Sample

Abstract: Purpose:Although patient-provider communication is an essential component of health care delivery, little is known about the quality of these discussions among patients with cancer.Methods:Data are from the 2011 Medical Expenditure Panel Survey Experiences with Cancer survey among 1,202 adult cancer survivors. We evaluated discussions with any provider after a cancer diagnosis about: (1) follow-up care; (2) late or long-term treatment effects; (3) lifestyle recommendations, such as diet, exercise, and quitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Previous studies have shown that CRC patients that have received dietary advice were more likely to change their diet, although lifestyle issued are not always adequately addressed by health care providers [20, 21]. Tan et al state that “clinicians could consider addressing issues including smoking cessation, physical activity, or other risk behaviours with their patients during the early survivorship period when patients are likely to be more receptive to information about managing risks of recurrence” [6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CRC patients that have received dietary advice were more likely to change their diet, although lifestyle issued are not always adequately addressed by health care providers [20, 21]. Tan et al state that “clinicians could consider addressing issues including smoking cessation, physical activity, or other risk behaviours with their patients during the early survivorship period when patients are likely to be more receptive to information about managing risks of recurrence” [6].…”
Section: Discussionmentioning
confidence: 99%
“…One third to one half of cancer survivors report suboptimal patient-centered communication [30]. Recent research has identified gaps in this area, noting that cancer survivors are not given detailed communication about follow-up care, lifestyle recommendations, or social and emotional needs [31]. Future curriculum content development should address how nurses should relay news of recurrence and initiate discussions about quality of life that include physical, psychological, social, and spiritual well-being domains.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers may also have a role to play in discussing expectations and decisions about cancer treatment and making appropriate referrals for rehabilitative, symptom management, and/or social work guided interventions. A recent nationally representative study of cancer survivors reported that less than half of cancer survivors report high quality discussions with providers, at any time following diagnosis, regarding late or long-term effects of cancer and treatment (Chawla, Blanch-Hartigan, & Virgo, 2016). Given the importance of work and the high levels of underemployment that many cancer survivors face, particularly married women, discussion about how cancer and its treatment may have an impact on work should be both systematically studied and recognized as a component of comprehensive survivorship care.…”
Section: Discussionmentioning
confidence: 99%